1974. Title: A novel low-dose self-amplifying mRNA vaccine (GRT-R910) induces strong and broad boost in cellular and humoral immune response following primary series with a chimpanzee adenovirus SARS-CoV-2 vaccination. (15th December 2022) - Turgut, Tolga; Ahmed, Uzma; Kachura, Melissa; Kraemer, Lauren; Nganje, Charmaine; Hart, Meghan; Jaroslavsky, Jason; Kounlavouth, Sonia; Marral, Martina; Venkatraman, Harshni; Kuan, J C; Palmer, Christine; et al.
Abstract: Disclosures: Ciaran Scallan, PhD, Gritstone Bio: Salaried employee of Gritstone|Gritstone Bio: Stocks/Bonds Andrew Ustianowski, MD, PhD, Gilead: Advisor/Consultant|Gilead: Board Member|Gilead: Honoraria|Gilead: Speaker fees|Pfizer: Honoraria|Pfizer: Speaker fees|Vir/GlaxoSmithKline: Advisor/Consultant|Vir/GlaxoSmithKline: Board Member. Background: The SARS-CoV-2 pandemic continues, with new variants of concern fueling periodic increases in COVID-19 cases. Authorized vaccines have provided protection against severe disease but less so for incident cases. Boosts with these vaccines have demonstrated waning protection. New vaccines, including those which induce immunity against more conserved regions outside of Spike, may improve upon these and be key to long-term protection and may be a useful approach against novel coronaviruses. Methods: GO-009 (CORAL-Boost, NCT05148962) is an open-label study, conducted in the UK, of a self-amplifying mRNA vaccine encoding for Wuhan Spike (S) and highly conserved non-S T cell epitopes (GRT-R910; R910). R910 is given as 1 or 2 doses after vaccination with an authorized adenovirus or mRNA SARS-CoV-2 vaccine. The first two cohorts assessed 10µg and 30µg doses of R910 in older (≥60y) adults who had previously received ChAdOx1. Subsequent cohorts assess two boost doses in older and younger adults who have received an adenovirus or mRNA vaccine. Primary objectives are safety and reactogenicity and secondary objectives include cellular and humoral immunogenicity. Results: Ten and seven adults received 10 or 30µg (cohorts 1 and 2) of R910, respectively. Reactogenicity and unsolicited adverse events were mostly mild/moderate and transient. The majority of severe events (malaise, fatigue, myalgia, Inj. site pain/tenderness/swelling) after dose 1 were experienced by 1 subject in cohort 2. Analysis of both IgG binding and neutralizing antibodies demonstrated a boost of anti-S antibodies after one dose of R910; geomean ID50 titers from 92 to 2370 and 99 to 1553 for 10 and 30µg, respectively. ELISpot analyses demonstrated that R910 boosted and broadened T cell responses to S and non-S T cell epitopes. Conclusion: R910 was well tolerated. One R910 boost vaccination increased existing humoral and cellular immunity against S while inducing a broad T cell response against non-S SARS-CoV-2 proteins. A 10µg R910 boost increased neutralizing antibody titers comparable to a 10-fold higher dose (100µg) with authorized mRNA vaccines in a similar population (Munro et al 2021). A 10µg dose was selected for further study. Data post mRNA primary series will also be presented.